Business triads in servitization; The influence of the provider's - partner relationship on the performance of the partner towards the provider - Karatzas, Antonios (Cranfield University, 2012)
The thesis is concerned with a problem arising in contexts where there is provision of integrated product-service offerings (servitization). It may be the case that the provider relies on independent service partners for the delivery of the services to the customer, which means that the three actors (provider, service partner and customer) form a triad. This makes the performance of the partner determinative for customer satisfaction and hence an important issue for the provider. Because the buyer – supplier relationships and business triads literatures suggest that relationships affect the performance of the related parties, the aim of this work is to understand how the provider – partner working relationship influences the service performance of the latter. To satisfy the aim, an appropriate setting in the UK commercial vehicles industry was identified (one provider plus a network of service partners), and a mixed-methods research design was employed. The qualitative part consisted of several exploratory interviews and three case-studies of purposively sampled provider – partner relationships. The quantitative part had a supplementary character, and as part of it, questionnaires completed by 38 of the provider’s partners were analyzed with the use of a configurational method (fsQCA). In this study, the firm-level working relationship was considered as a five-dimensional construct based on Cannon’s and Perreault’s (1999) framework of relationship connectors. The findings consist of: 1) A model capturing the causal ordering of the relationship dimensions, their interplay with two emergent exogenous factors, and their eventual impact on the service performance of the partner. 2) A set of configurations of relationship dimensions and exogenous factors enhancing service performance. With the in-depth study of the influence of the provider – partner relationship on the performance of the partner towards the provider’s customer-base, my research simultaneously contributes to knowledge in two ways. Firstly, it helps in the theoretical development of the phenomenon of servitization, and secondly, it extends triadic research by examining in depth and in a novel setting the relationship – performance interdependence within the triad.